Shared neoantigens’ atlas for off-the-shelf cancer vaccine development - Angela Mauriello; Beatrice Cavalluzzo; Concetta Ragone; Maria Tagliamonte; Luigi Buonaguro (Journal of Translational Medicine)
Abstract Background We have recently described that the most prevalent 100 mutations identified in human cancers, both single nucleotide variations (SNVs) and InDels, generate a handful number of shared mutated neoantigens (SNV and InDel-NeoAgs) in association with 5 HLA-A and 7 B haplotypes. Methods In the present study, we expanded such analysis to 50 haplotypes in the three MHC class I loci (10 HLA-A, 27 HLA-B and 13 HLA-C), including all the mutated proteins identified in at least 5% of cancer patients. Results Overall, the extended analysis identified 15 SNV-NeoAgs and 55 InDel-NeoAgs with a significant affinity improvement over the corresponding wt (DAI > 10). These targetable shared NeoAgs are prevalently derived from PIK3CAH1047R (6/15 SNV-NeoAgs) and LARP4BT163Hfs (30/55 InDel-NeoAgs). From the HLA perspective, the HLA-A*33:03 is associated with the largest number of SNV-NeoAgs (4/15 NeoAgs) and the HLA-B*58:01 is associated with the largest number of InDel-NeoAgs (16/55 NeoAgs). According to the distribution of each HLA haplotype in at least 10% of the regional populations, therapeutic cancer vaccines based on mutated shared SNV and InDel-NeoAgs, might be developed for COAD, STAD and UCEC cancers, with a global coverage, and for PAAD and UVM, with a regional coverage. Conclusions This represents the first in-depth analysis for the identification of a specific repertoire of shared mutated NeoAgs, most of which never reported before. Such shared SNV and InDel-NeoAgs are indispensable for the development of “off-the-shelf” cancer vaccines targeting a relevant percentage of cancers in a significant percentage of cancer patients worldwide.